Peran Good Corporate Governance dalam Meningkatkan Kualitas Pelayanan dan Loyalitas Nasabah Koperasi Syariah - Madinah, Salsabilatul; Farida, Alimatul; Mundir, Abdillah (Kartika: Jurnal Studi Keislaman, 2025)
This study aims to analyze the role of Good Corporate Governance (GCG) in enhancing service quality and customer loyalty at BMT UGT Nusantara, a Sharia-based microfinance institution that upholds the principles of transparency, accountability, and fairness. The implementation of GCG is considered a key factor in building public trust and fostering long-term relationships between the institution and its members. Using a quantitative approach, primary data were collected through Likert-scale questionnaires administered to 100 active customers of BMT UGT Nusantara, supported by secondary data from financial reports and institutional documents. The findings reveal that GCG has a positive and significant effect on service quality, which subsequently strengthens customer loyalty. The assurance and reliability dimensions emerged as the most influential aspects in shaping customers’ positive perceptions of service performance. These results demonstrate that sound governance practices not only improve internal efficiency and compliance with Sharia principles but also enhance customer trust and satisfaction. The study concludes that consistent application of GCG principles across all operational activities is essential for improving competitiveness and ensuring the long-term sustainability of Sharia microfinance institutions.